Exploring the Artistic Development Stage of Dürer's Prints: Taking Rhinoceros as an Example - Zhang, Boya (Transactions on Social Science, Education and Humanities Research, 2024)
Albrecht Dürer is an important artist in the German Renaissance. Born in Nuremberg, Germany in 1471, he showed a great artistic talent in his childhood. Throughout his life, he devoted himself to helping Germany get rid of the shackles of Gothic art, thus leading Germany towards humanism. Albrecht Dürer created many works, including woodcut, print, and other aspects, reflecting his deep study of anatomy and perspective. Of his many works of art, "Rhinoceros" may not be the most perfect or influential, but its background makes it hard to lose interest. When it was created in 1515, the painter Dürer himself had never even seen the Indian rhino before, but it was based on the manuscripts and imagination of others. Although the woodcut "Rhinoceros" is far from the modern rhinoceros, the work shocked society and overturned the perception at that time. In conclusion, Albrecht Dürer's contributions were instrumental in the advancement of the German Renaissance, promoting a shift towards humanism and more realistic representations in art. His works not only reflect his deep understanding of human anatomy and perspective but also his innovative spirit and ability to influence public perception through art. The legacy of Dürer's artistic achievements continues to be recognized for their impact on the evolution of Western art.